2010
DOI: 10.1084/jem.20091738
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 acts directly on B cells to regulate Bcl-6 expression and germinal center responses

Abstract: During T cell–dependent responses, B cells can either differentiate extrafollicularly into short-lived plasma cells or enter follicles to form germinal centers (GCs). Interactions with T follicular helper (Tfh) cells are required for GC formation and for selection of somatically mutated GC B cells. Interleukin (IL)-21 has been reported to play a role in Tfh cell formation and in B cell growth, survival, and isotype switching. To date, it is unclear whether the effect of IL-21 on GC formation is predominantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
695
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 669 publications
(756 citation statements)
references
References 47 publications
57
695
3
1
Order By: Relevance
“…The absence of IL-21 in the supernatants of CD4 + splenocytes with porin peptide-pulsed DCs and the lack of significantly altered anti-porin Ab responses in Il21r-deficient animals suggest that this cytokine does not play a role in the IgM GC B cell response. This finding is in line with a previous study showing that IL-21 is not required for the protective Ab response against Salmonella infection (58). However, IL-21 may provide critical support for IgM to IgG Ig switch during infection with other Gram-negative bacteria such as Ehrlichia muris (59), suggesting that these bacteria imprint a different cytokine pattern during infection.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of IL-21 in the supernatants of CD4 + splenocytes with porin peptide-pulsed DCs and the lack of significantly altered anti-porin Ab responses in Il21r-deficient animals suggest that this cytokine does not play a role in the IgM GC B cell response. This finding is in line with a previous study showing that IL-21 is not required for the protective Ab response against Salmonella infection (58). However, IL-21 may provide critical support for IgM to IgG Ig switch during infection with other Gram-negative bacteria such as Ehrlichia muris (59), suggesting that these bacteria imprint a different cytokine pattern during infection.…”
Section: Discussionsupporting
confidence: 91%
“…29 It has been reported that IL-21 improves the differentiation of Tfh cells by inducing Bcl6 and Cxcr5 mRNA in vitro. [30][31][32] Recently, Th1-like Tfh cells were proposed in many studies, which could express Th1 effector cytokine IFN-g and Tfh effector cytokine IL-21 in the same time. 20,21 In our previous studies, we found that the percentage of IL-21 C IFN-g C CD4 C cells was significantly higher in nasal polyp (NP) tissues compared with control tissues and matched PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…GCs are comprised of B cells and Tfh cells (which migrate into GCs following initial interaction with B cells at the margin of the B‐cell follicle), together with antigen‐bearing follicular dendritic cells (FDCs), macrophages, and stromal cells. B cells undergo further cognate interactions with Tfh cells in the light zones of the GC, in which help is again mediated via two‐way receptor‐ligand interactions and production of cytokines including IL‐21 102, 103, 104. This enables Tfh cells to control the affinity of B cells entering the GC reaction 105.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%